Peculiarities of the language teaching professional communication at the final stage. - Тростинская, О. Н.; Санина, Л. П.; Копылова, Е. В. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2016)
The article analyzes the peculiarities of language teaching professional communication in foreign undergraduates and graduate students enrolled in the final stage, and give the methodological recommendations on the formation of professional competence (language and speech) organization of the scientific work of this category of students